2023
DOI: 10.3389/fphar.2023.1047184
|View full text |Cite
|
Sign up to set email alerts
|

Niaoduqing alleviates podocyte injury in high glucose model via regulating multiple targets and AGE/RAGE pathway: Network pharmacology and experimental validation

Abstract: Purpose: The aim of present study was to explore the pharmacological mechanisms of Niaoduqing granules on the treatment of podocyte injury in diabetic nephropathy (DN) via network pharmacology and experimental validation.Methods: Active ingredients and related targets of Niaoduqing, as well as related genes of podocyte injury, proteinuria and DN, were obtained from public databases. Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and protein-protein interaction (PPI) network analysis were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Niaoduqing granules can be used to effectively treat proteinuria in patients with DKD. Through network pharmacology, it has been found that the mechanism of Niaoduqing granules in treating DN proteinuria is to inhibit the activity of the AGE/RAGE pathway and the overexpression of VEGF-A, ICAM-2, PTGS-5, and ACE in MPC1 cells to prevent podocyte injury in DN [110]. However, evidence of adverse drug reactions remains unclear [111].…”
Section: Other Chinese Patent Medicinementioning
confidence: 99%
“…Niaoduqing granules can be used to effectively treat proteinuria in patients with DKD. Through network pharmacology, it has been found that the mechanism of Niaoduqing granules in treating DN proteinuria is to inhibit the activity of the AGE/RAGE pathway and the overexpression of VEGF-A, ICAM-2, PTGS-5, and ACE in MPC1 cells to prevent podocyte injury in DN [110]. However, evidence of adverse drug reactions remains unclear [111].…”
Section: Other Chinese Patent Medicinementioning
confidence: 99%
“…The increase of intracellular adhesion molecule-1 (ICAM-1), tumor necrosis factor (TNF), interleukin-1 and interleukin -6 and the infiltration and functional activity of macrophages, neutrophils, fibrosis and mast cell in the kidney and their functional activity are important driving factors of renal inflammation and fibrosis. [8][9][10] Over the past decade, many potential diagnostic markers have been discovered for this condition. [11] Serum TNF receptors 1 and 2 are significantly correlated with certain inflammation-related DN precocious glomerular lesion types.…”
Section: Introductionmentioning
confidence: 99%